Variable Universe Fuzzy Control of Soft-start for Asynchronous Motor - GAO Chunxia; LI Linbo; LIU Xiuhong (Kongzhi Yu Xinxi Jishu)
Soft-start system of asynchronous motor is a typical time-varying, non-linear system. The instantaneous impact of the starting current is large, which has a great influence on the motor, the drive equipment and the power grid. In this paper, a variable domain fuzzy PID controller based on variable domain fuzzy PID control method was designed to solve the problem that traditional PID controllers have poor control effect when it is used to control motor starting current. Variable domain fuzzy PID controller was introduced to the softstart control of asynchronous motors. By selecting appropriate fuzzy rules and scaling factors, the optimization of PID parameters can be achieved. The simulation results show that the controller has the advantages of fast response, high precision, and strong anti-interference.